Pemanfaatan Senyawa Hepatoprotektif dalam Ekstrak Lumut Hati (Marchantia polymorpha) Sebagai Obat Hepatitis Berdasarkan Penurunan SGOT SGPT - Deanoval, Alfito; Suharti, Peni; Salsabillah, Adilla Wahyuni; Prastyo, Muhammad Rendi; Mufidah, Melli; Qoimah, Siti Nur (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Bryophyta plants contain secondary metabolite compounds that can have potential as drugs, such as liverwort (Marchantia polymoprha) which contains secondary metabolite compounds that have hepatoprotective properties against liver damage that have the potential as hepatitis drugs. The purpose of this study was to describe the effect of liverwort extract administration in treating hepatitis. This study used an experimental approach, with a postest only control group design, 16 male white rats (Rattus norvegicus) were grouped into 4 treatments with dose variations of 200 mg / kgBB, 300 mg / kgBB, 400 mg / kgBB, 500 mg / kgBB. Experimental animals were induced with 30% alcohol for 10 days to be exposed to hepatitis, and given treatment for 14 days. Data were analyzed by One Way Anova test, with a significance of 0.05, normally distributed data with a significance of SGOT 0.20 and SGPT 0.81. The results of data analysis showed that the concentration of 500 mg/kgBB extract dose had the strongest effect in reducing SGOT and SGPT enzymes.